О природе и некоторых особеннocтях целевых конструкций с инфинитивом (на материале современного английского языка) - Мацелите, Виктория (Kalbotyra, 1987)
The paper focuses on the problem of the semantic relations of purpose and cause in the infinitival construction expressing purpose and also on some peculiarities of their use with conjunctions. The data obtained suggest that the conjunction in order is used mainly to avoid ambiguity, whereas the conjunction so as differs from the conjunction in order in meaning.